Hypnobirthing sebagai Self Hypnosis dalam Menurunkan Tingkat Kecemasan Ibu Hamil - Legina Anggraeni; Dinni Randayani Lubis (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Hypnobirthing is a way to reduce anxiety and has no effect on fetal growth and development. The purpose of this study was to determine the effect of hypnobirthing as self hypnosis in reducing anxiety in pregnant women. This study used a quasi-experimental design with a sample size of 50 people. The location for data collection was the Independent Practice Midwife in the Jakarta area. Mother's anxiety level was measured before and after being given hypnobirthing using the HARS questionnaire. Data were analyzed using the Wilcoxon sign test. The results of the analysis showed that the p-value = 0.0001 or there was a difference in the level of anxiety between before and after being given hypnobirthing. Furthermore, it is concluded that hypnobirthing is effective for reducing anxiety in pregnant women.Keywords: hypnobirthing; pregnancy; worryABSTRAK Hypnobirthing merupakan cara untuk mengurangi kecemasan dan tidak memiliki pengaruh terhadap pertumbuhan dan perkembangan janin. Tujuan penelitian ini adalah untuk mengetahui pengaruh hypnobirthing sebagai self hypnosis dalam menurunkan kecemasan ibu hamil. Penelitian ini menggunakan desain kuasi eksperimental dengan ukuran sampel 50 orang. Lokasi pengambilan data adalah Bidan Praktik Mandiri wilayah Jakarta. Tingkat kecemasan ibu diukur sebelum dan sesudah diberikan hypnobirthing menggunakan kuesioner HARS. Data dianalisis menggunakan adalah Wilcoxon sign test. Hasil analisis menunjukkan nilai p = 0,0001 atau ada perbedaan tingkat kecemasan antara sebelum dan sesudah diberikan hypnobirthing. Selanjutnya disimpulkan bahwa hypnobirthing efektif untuk menurunkan kecemasan ibu hamil.Kata kunci: hypnobirthing; kehamilan; kecemasan